Teacher Education, Aboriginal Studies and the New National Curriculum - Andersen, Clair (The Australian Journal of Indigenous Education, 2012)
Aboriginal and Torres Strait Islander students in Australian schools continue to have poor education and health outcomes, and the introduction of a new national curriculum may assist in redressing this situation. This curriculum emphasises recommendations which have been circulating in the sector over many years, to require teacher education institutions to provide their students with an understanding of past and contemporary experiences of Indigenous Australians, as well as the social, economic and health disadvantages that challenge Indigenous communities, and to equip them to integrate Indigenous issues into their future teaching programs. This article, while focusing on teacher education developments at the University of Tasmania (UTAS) to meet National Standards and Frameworks for preservice teachers, provides some general background, and identifies recently developed resources, including the potential for Indigenous centres within universities to assist educators.